Approximation methods to solve a single machine scheduling problem with fuzzy due date to minimize multi-objective functions - et. al., Hanan Ali Chachan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper present three methodant colony optimization (ACO), particle swarm optimization (PSO) and bees algorithm optimization (BAO) to the solution multi-objective function of single machine problem with the fuzzy due date. The objective function to minimize total completion time and maximum lateness with a fuzzy due date. By a computer simulation used to compare the performance of each algorithm with another one from where accuracy and time.